Predictors of happiness among older Korean women living alone. Issue 4 (11th February 2019) - Kim, Jongim; Song, Youngshin; Kim, Taehee; Park, Keumok
Abstract : Aim: The level of happiness of older adults is associated with their psychosocial and physical health. Currently, little is known about the predictors of happiness among older women living alone in the community. The present study aimed to identify these predictors. Methods: This was a cross‐sectional descriptive study of older women who were living alone and were registered with a social welfare center in an old urban area in South Korea. We designated various demographic factors along with health‐related information, perceived self‐esteem and depressive symptoms as independent variables predicting happiness. Descriptive statistics and multivariate analysis were carried out. Results: In total, 154 participants were recruited. They showed a moderate level of happiness. Furthermore, happiness was negatively correlated with the number of comorbidities, presence of pain and depressive symptoms, but positively correlated with self‐esteem. The final model in hierarchical regression showed that depressive symptoms were powerful predictors of happiness after controlling the covariates and accounted for approximately 76.7% of the total variances. Conclusions: The happiness of older women living alone was associated with their self‐esteem and depressive symptoms. Interventions aimed at reducing depressive symptoms and improving self‐esteem should be developed and applied to this population. Geriatr Gerontol Int 2019; 19: 352–356 .